2020
DOI: 10.1161/strokeaha.120.030150
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography Might Improve Diagnosis of Acute Stroke and Large Vessel Occlusion

Abstract: Background and Purpose: Clinical methods have incomplete diagnostic value for early diagnosis of acute stroke and large vessel occlusion (LVO). Electroencephalography is rapidly sensitive to brain ischemia. This study examined the diagnostic utility of electroencephalography for acute stroke/transient ischemic attack (TIA) and for LVO. Methods: Patients (n=100) with suspected acute stroke in an emergency department underwent clinical exam then electroen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 11 publications
(34 reference statements)
1
64
0
Order By: Relevance
“…A previous small study of 24 suspected stroke patients found that the alpha-delta ratio, the (delta*theta)/(alpha*beta) ratio, delta power and lower beta power discriminated between patients with and without an AIS with a large infarct volume, in a population of suspected stroke patients in the ER [16]. In another study, dry electrode EEG recordings were performed in 100 patients with suspected or definite stroke in the ER [17]. In this study, the relative theta power and relative alpha power combined identified LVO-a stroke with an AUC of 0.69.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous small study of 24 suspected stroke patients found that the alpha-delta ratio, the (delta*theta)/(alpha*beta) ratio, delta power and lower beta power discriminated between patients with and without an AIS with a large infarct volume, in a population of suspected stroke patients in the ER [16]. In another study, dry electrode EEG recordings were performed in 100 patients with suspected or definite stroke in the ER [17]. In this study, the relative theta power and relative alpha power combined identified LVO-a stroke with an AUC of 0.69.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalography (EEG) may be an alternative to boost diagnostic accuracy of prehospital LVO-a stroke identification. Recently, two small studies performed in an emergency department setting have provided preliminary data that suggest that EEG could be a feasible instrument for detection of LVO-a stroke [16,17]. Although traditional EEG measurement requires long preparation times, solutions for faster and easier application are available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of these studies was mixed, with a median score of 3 (range 2-4). Four reported that relative spectral power detected large infarct volume (more common in LVO), either by identifying areas of increased slower-waves (delta [11,21] and theta [22]) and/or decreased fast-waves (beta [21,38] and alpha [22]). Epileptiform activity (including slowing of frequencies) differentiated between territorial infarcts more typical of LVO and sub-cortical infarcts more likely to result from small vessel ischaemia [39].…”
Section: B) Identi Cation Of Ischaemic Versus Haemorrhagic Strokementioning
confidence: 99%
“…There has been growing utilization of EEG for diagnosis and monitoring of neurological disorders such as stroke 6 , and concussion 7 . Common imaging methods for detecting brain damage, e.g., magnetic resonance imaging (MRI) 8,9 , or computed tomography 10 , are not portable, are not designed for continuous (or frequent) monitoring, are difficult to use in many emergency situations, and may not even be available at medical facilities in many countries.…”
mentioning
confidence: 99%